Cardiopulmonary exercise testing for the prediction of morbidity risk after rectal cancer surgery. Issue 9 (11th June 2014) - West, M. A.; Parry, M. G.; Lythgoe, D.; Barben, C. P.; Kemp, G. J.; Grocott, M. P. W.; Jack, S.
<x xml:space="preserve">Abstract</x> Background This study investigated the relationship between objectively measured physical fitness variables derived by cardiopulmonary exercise testing (CPET) and in‐hospital morbidity after rectal cancer surgery. Methods Patients scheduled for rectal cancer surgery underwent preoperative CPET (reported blind to patient characteristics) with recording of morbidity (recorded blind to CPET variables). Non‐parametric receiver operating characteristic (ROC) curves and logistic regression were used to assess the relationship between CPET variables and postoperative morbidity. Results Of 105 patients assessed, 95 (72 men) were included; ten patients had no surgery and were excluded (3 by choice, 7 owing to unresectable metastasis). Sixty‐eight patients had received neoadjuvant treatment. ROC curve analysis of oxygen uptake (<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pghrq79dz2" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />V˙</alternatives>o2) at estimated lactate threshold (<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pghrq79dsg" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />θ^</alternatives>L) and peak <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pghrq79dt0" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />V˙</alternatives>o2 gave an area under the ROC curve of 0·87 (95 per cent confidence interval 0·78 to 0·95; P < 0·001) and 0·85 (0·77 to 0·93; P < 0·001) respectively, indicating that they can help discriminate patients at risk of postoperative morbidity. The optimal cut‐off points identified were 10·6 and 18·6 ml per kg per min for <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pghrq79dmw" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />V˙</alternatives>o2 at <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pghrq79dqf" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />θ^</alternatives>L and peak respectively. Conclusion CPET can help predict morbidity after rectal cancer surgery.